XPS valence band study of Na‐silicate glasses: energetics and reactivity. (4th July 2017) - Nesbitt, H. W.; Bancroft, G. M.; Ho, R.
Abstract : High‐resolution X‐ray photoelectron spectroscopy (XPS) of valence bands of vitreous silica (SiO2 (vit)), and Na‐silicate glasses are divisible into 3 sub‐bands. These are the O 2s band, the lower valence band (LVB), and the upper valence band (UVB). Many peaks of the LVB and UVB have line widths (full width at half maximum) of 1.2–1.7 eV, which are commensurate with widths of core level O 1s lines, indicating weak dispersion of these valence band peaks. Two types of oxygen exist in the glasses. There is oxygen bridging 2 Si atoms (bridging oxygen [BO]), and O bonded to Si and Na (nonbridging oxygen [NBO]). The addition of Na to siliceous glasses diminishes electronic density of states of the LVB and enhances density of states of the UVB, a consequence of quenching Si‐BO σ‐bonds of the LVB, creating Si‐NBO σ‐bonds in the UVB, and creating atomic‐like O 2p x, y nonbonding orbitals at the top of the UVB or highest occupied molecular orbitals. The process destabilizes the valence bands of the glasses by 2 to 6 eV per Si‐NBO bond formed. All orbitals are destabilized with increased Na2 O content. There is effectively complete transfer of Na 3s electrons to NBO but this charge is redistributed among all atoms of the tetrahedron via the 4 Si‐O σ bonds (sp 3 ‐O 2p x character). The BE of the Si 2p line decreases more rapidly with Na2 O content than any other line monitored, and this preferential accumulation of negative charge on Si causes Si‐O bonds to become weaker through decrease in the force constant of the bonds. The durability of Na‐silicate glasses decreases in response. The destabilization of the highest occupied molecular orbitals makes the Na‐rich glasses more susceptible to attack by reagents such as H +, OH −, and H2 O. Copyright © 2017 John Wiley & Sons, Ltd.